Impact of providing patients with copies of their medical correspondence: a randomised controlled study. Issue 1 (January 2017) - Fenton, C.; Al‐Ani, A.; Trinh, A.; Srinivasan, A.; Marion, K.; Hebbard, G.
Abstract : Background: In Australia, correspondence is routinely sent to general practitioners following a specialist consultation. Written communication is an important way to enhance patient experiences and understanding, yet most patients do not receive copies of their medical correspondence. Aims: To determine whether providing clinic correspondence and endoscopy reports to patients leads to improved understanding, satisfaction or anxiety. Methods: This is a prospective, randomised controlled study conducted at an Australian tertiary hospital from October 2013 to February 2015. New adult referrals to the general gastroenterology clinic requiring an urgent endoscopic procedure were eligible for the study. The intervention group received a copy of their clinic correspondence and endoscopy report, while the control group received neither. Participants completed questionnaires, including visual analogue scales and the Hospital Anxiety and Depression Scale, at three time points. Primary outcomes were patient understanding, anxiety and satisfaction. Results: A total of 70 participants was included in the study. There was no reduction in anxiety levels ( P  = 0.52), no increase in understanding ( P  = 0.73) or any increase in satisfaction ( P  = 0.33) in participants receiving correspondence. However, 97% of participants indicated that they wished to receive correspondence in the future, and 94% of participants in the correspondence group reported that receiving correspondence had helped them to understand their medical condition. Conclusion: Patients wish to receive copies of their correspondence and feel it improves their understanding of their medical condition. Although we were unable to demonstrate a measurable reduction in anxiety, increase in understanding or satisfaction, we recommend that patients be offered the choice of receiving copies of their clinic correspondence and endoscopy reports.